An Understanding of Identity in the Gestalt Psychotherapy - Stamenković, Barbara (Array, 2010)
The aim of the lecture is to articulate an intriguing understanding of identity in humanistic, experiential and holistic Gestalt psychotherapy, starting from the works of Perls, Yontef, Buber and Jacobs. An understanding of identity in the Gestalt psychotherapy is unique for its insisting on awareness, contact, dialogic process, experiment and authenticity. Identity is seen as a dynamic construct that forms through the process of awareness, at the contact boundary between organism and field, in the dynamic exchange of figures and ground, in the proliferation of the personas. "Authentic" identity is understood as a "continuing creative adjustment" and "change of different parts of self with whom we reach contact". "Authentic" identity transcends the rigidity of the "character", is "organismicaly self-regulating" and enters the contact with full "sensory-motor-emotional-cognitive support". "Authentic" identity is achieved through awareness of resistances and neurotic mechanisms that block the cycle of contact, awareness and reintegration of unclaimed polarities, finishing unfinished business and experimenting with different parts of self in "here and now" of the therapeutic dialogic relationship.